Human Papillomavirus, Cytomegalovirus Infection and P16 Staining in Breast Tumors from Peruvian Women - Calderon-Valencia, G (2022)
Objective: To evaluate the frequency distribution of viral infections in Peruvian Breast Cancer (BC) lesions and its association with clinicopathological features. Additionally, a prospective evaluation of p16 and Tumor-infiltrating lymphocytes (TIL) levels were performed for developing a comprehensive analysis. Methods: Detection of high risk- human papillomavirus (HR- HPV) through qPCR was performed in 447 BC and 79 non-cancer frozen samples. Paired paraffin samples from 238 BC were stained with Human cytomegalovirus (HCMV) and p16 immunohistochemistry. TIL was calculated in 397 BC cases. Results: HCMV was positive in 72.5%. HR- HPV was detected in 2.9% of BC and 1.3% of non-malignant samples. P16+ was found in 28.15% and median TIL percentage was 30. HR- HPV infection was associated with non-ductal histology (p=0.003) and p16+ (p=0.017). Positive P16+ was associated with higher T stage (p=0.022), grade (p=0.009), TIL level (p=0.002), and triple-negative phenotype (p=0.021). Conclusion: HCMV is frequent, but HR- HPV infection is unusual in Peruvian BC. P16+ is associated with HR- PVH infection, high TIL and aggressive features. © 2022. All Rights Reserved.